Improving the State Budget - Primova Nigora Ikram kizi (European Journal of Life Safety and Stability (2660-9630), 2023)
This article presents opinions on ways to improve the state and local budget of the Republic of Uzbekistan. In addition, suggestions and recommendations were developed regarding the proper distribution of local budget funds, improvement of the budget situation.